EU Carbon Futures Market: The Aspects of Price Discovery - Kropienė, Rūta; Karpavičiūtė, Daina (Lithuanian Journal of Statistics, 2011)
The main purpose of this article is to study the relationship between the spot and future price of European emissionallowances in order to test market efficiency hypothesis and determine which price leads the price discovery process.The work consists of several parts: presentation of theoretical background of model cost of carry; validation of cost of carrymodel assumptions; analysis of price development and conclusion.The cost of carry and cointegration theory is provided as well as overview of the related literature and existing research.The empirical examination reveals structural breaks in data and evidence that spot and futures prices are linked by the cost-ofcarryapproach in the second half of the analysed period. The examination of price development in the market indicated futures price leadership.Conclusion summarized the main results of the performed research.
Keywords: European Emission Allowances; Carbon Future market; Cost of carry model